Management and wisdom. Establishing some connections (2008)
What kind of links can be established between management and wisdom? The world’s current problems (e.g. poverty, inequality, corruption, environmental degradation, etc.) suggest that the impact of some management theories and practices are not always benefi cial for humankind. With the purpose of contributing to humanizing management, the notion of wisdom and its diverse meanings are evoked here. A theoretical framework is proposed to associate wisdom to various dimensions of management. In order to draw some links, we recur to literary quotations offering useful sensitizing strategies and allowing us to ascertain that we can discover sources of wisdom in all human beings in general and seniors in particular.